Optimization of Behavioral Segmentation-Based Omnichannel Strategies in Managing the Student Journey Experience at Private Universities in Indonesia: A Conceptual Review - Muhammad Ardiansyah; Muhammad Amir Anshori (Universitas KH. Abdul Chalim Mojokerto, 2026)
The increasing reliance of students on both digital and physical channels necessitates private universities to manage interactions and services in a more integrated and cohesive manner. An omnichannel strategy represents a relevant approach; however, its implementation in higher education institutions remains largely partial and predominantly focused on marketing communication. As a result, it has yet to effectively manage the student journey experience in a comprehensive manner. This study aims to develop a conceptual framework for optimizing omnichannel strategies based on student behavioral segmentation in managing the student journey experience at private universities in Indonesia. Employing a qualitative approach, this research adopts a narrative literature review guided by PRISMA principles, examining scholarly publications from the past five years indexed in the Scopus and SINTA databases. The findings indicate that omnichannel integration lacking a behavioral understanding of students tends to produce experiences that are generic, fragmented, and unsustainable. This study concludes that behavioral segmentation should be positioned as a fundamental basis for strategic decision-making in omnichannel management, enabling the design of contextual and consistent student experiences across all stages of the academic journey. The implications of this research provide a conceptual foundation for universities to develop adaptive, cross-channel integrated student experience management systems that support the sustainability of long-term relationships between institutions and students.